2021
DOI: 10.1186/s12885-021-07782-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal biological dose: a systematic review in cancer phase I clinical trials

Abstract: Background Classical phase 1 dose-finding designs based on a single toxicity endpoint to assess the maximum tolerated dose were initially developed in the context of cytotoxic drugs. With the emergence of molecular targeted agents and immunotherapies, the concept of optimal biological dose (OBD) was subsequently introduced to account for efficacy in addition to toxicity. The objective was therefore to provide an overview of published phase 1 cancer clinical trials relying on the concept of OBD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…To examine that our approach can be translated to real clinical settings beyond a cellular level, we further validated the simulated toxicity with clinical as well as pre-clinical studies (see Supplementary Note). Considering the maximum tolerated dose (MTD), which is the toxicity measurement for patients in clinical phase I 30 , we calculated simulated MTD (sMTD) of the control network (see Methods). We found that MTD of a BCL2 inhibitor is higher than that of an AKT inhibitor, as sMTD of BCL2 perturbation is higher than that of AKT perturbation in the control network.…”
Section: Resultsmentioning
confidence: 99%
“…To examine that our approach can be translated to real clinical settings beyond a cellular level, we further validated the simulated toxicity with clinical as well as pre-clinical studies (see Supplementary Note). Considering the maximum tolerated dose (MTD), which is the toxicity measurement for patients in clinical phase I 30 , we calculated simulated MTD (sMTD) of the control network (see Methods). We found that MTD of a BCL2 inhibitor is higher than that of an AKT inhibitor, as sMTD of BCL2 perturbation is higher than that of AKT perturbation in the control network.…”
Section: Resultsmentioning
confidence: 99%
“…We believe the preclinical data presented here provide strong rationale to pursue clinical testing of bisteric inhibitors regardless of the effects seen in ongoing studies with allosteric inhibitors such as temsirolimus. In addition to measuring pharmacokinetics and determining a maximally tolerated dose, response biomarkers to determine optimal biological dosing ( 41 ) will be essential to make sense of potentially conflicting data between these 2 classes of inhibitors. Prior studies have confirmed the prognostic impact of multiparameter mTOR pathway activation in RMS, including phosphorylation of both RPS6 and 4EBP1 ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Optimal biological dose (OBD) is generally de ned as the lowest tolerable dose providing the highest rate of e cacy in patients 30 . The "sweet spot" we de ned here is the dose that provides the drug's saturated biological activity while being able to be safely administered.…”
Section: Discussionmentioning
confidence: 99%